Enhanced Corrosion Resistance of Co-Sn Alloy Coating with a Self-Organized Layered Structure Electrodeposited from Deep Eutectic Solvent. Issue 1 (1st January 2015) - Zhang, J. L.; Gu, C. D.; Fashu, S.; Tong, Y. Y.; Huang, M. L.; Wang, X. L.; Tu, J. P.
Abstract : Co-Sn alloy coatings are electrodeposited from a choline chloride/ethylene glycol eutectic-based electrolyte, named Ethaline, containing CoCl2 ·6H2 O and SnCl2 ·2H2 O without any complexing agent or additive. Cyclic voltammetry shows that the co-electrodeposition of Sn and Co is feasible due to the adjacent reduction potentials of Sn(II) and Co(II) in the solution. X-ray diffraction reveals that the films mainly contain Co3 Sn2 with expanded lattice parameters and pure Sn phases. Interestingly, a self-organization of layered structure with different Co content for each layer and mixed amorphous-nanocrystalline phases are formed in the electrodeposited film, which is revealed by cross-section transmission electron microscopy observations. The formation mechanism of the layered film is discussed based on the particular fluctuation of the current-time curve. The layered Co-Sn alloy coating with a total thickness of about 400 nm exhibits enhanced corrosion resistance showing a corrosion potential of −326 mV (vs. Ag/AgCl) and a corrosion current density of about 0.09 μA cm −2 in a 3.5 wt.% NaCl aqueous solution.